Neonatal Leukemoid Reaction: A Diagnostic Dilemna - Bhatia, Ravi; Bhatia, Gunjan (Journal of Nepal Paediatric Society, 2017)
Leukemoid reaction is defined as an absolute neutrophil count(ANC) of >30,000/cumm. First described by Holland and Maurer in 1963 leukemoid reaction is associated with infection, anemia, bronchopulmonary dysplasia, use of antenatal steroids, prematurity. Neonatal leukemoid reaction is seen as a neonatal response to hypoxia and can mimic leukemia. In our case the baby was premature and the leukemoid reaction was due to early onset sepsis. Clinicians need to keep sepsis in mind while dealing with neonatal leukemoid reaction. J Nepal Paediatr Soc 2016;36(3):298-299